Design and development of a self-balancing scooter: material selection and interfacing of a self-balancing scooter / Ezham Haznal Zahariman. - Zahariman, Ezham Haznal (2009)
The aim of this project is to select and implement a suitable component and material for the Self-balancing Scooter so that the prototype of the scooter can move forward and backward. The self-balancing scooter is a two wheeled self-balancing vehicle which is capable of carrying via the wheels underneath the rider's centre of gravity. It involves the program and application of the control system to perform specific task. The programming will control the movement of the scooter. A small scale model of the self-balancing scooter will be developed and will be integrated with the program. To implement the project, the main consideration will be on the component and material selection for the development of the scooter. This will be interfaced between the design part which is the hardware and the control part which is the program. Therefore it is important to select a suitable component and material for the scooter so that the scooter will be fabricated based on the suitable components and materials.